2013
DOI: 10.1093/jnci/djt032
|View full text |Cite
|
Sign up to set email alerts
|

Quadrivalent Human Papillomavirus Vaccine Effectiveness: A Swedish National Cohort Study

Abstract: BackgroundIncidence of condyloma, or genital warts (GW), is the earliest possible disease outcome to measure when assessing the effectiveness of human papillomavirus (HPV) vaccination strategies. Efficacy trials that follow prespecified inclusion and exclusion criteria may not be fully generalizable to real-life HPV vaccination programs, which target a broader segment of the population. We assessed GW incidence after on-demand vaccination with quadrivalent HPV vaccine using individual-level data from the entir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
85
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 19 publications
7
85
2
4
Order By: Relevance
“…Most Western countries have implemented national HPV vaccination programs for young girls, and countries withschool‐based vaccination programs tend to have the highest vaccine uptake 5, 6. To provide the best protection, the vaccine should be administered to young girls7 before they become sexually active 3. In Sweden, all children are offered vaccinations free of charge in the national vaccination program.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most Western countries have implemented national HPV vaccination programs for young girls, and countries withschool‐based vaccination programs tend to have the highest vaccine uptake 5, 6. To provide the best protection, the vaccine should be administered to young girls7 before they become sexually active 3. In Sweden, all children are offered vaccinations free of charge in the national vaccination program.…”
mentioning
confidence: 99%
“…Studies performed in Sweden before the national program was implemented provided conflicting results. For example, Dahlstrom et al14 indicated that parents with a higher level of education were less likely to accept the HPV vaccination, but a register study by Leval et al found the opposite 7. Ethnicity also seems to have a mixed effect on vaccine uptake.…”
mentioning
confidence: 99%
“…42 Similar findings were observed for the quadrivalent HPV vaccine in a study including over 2.2 million females aged 10-44 y, where increased vaccine effectiveness with decreasing age was noted. 43 Together with the fact that 5-15% of sexually active, middleaged adult women acquire a new oncogenic HPV infection each year (1-2% HPV 16/18), 40 these outcomes confirm that midadult women could potentially benefit from the vaccine. However, vaccination in this group of women cannot replace screening.…”
Section: Human Papillomavirus (Hpv) Vaccinationmentioning
confidence: 91%
“…[41][42][43][44] However, episodes of mass psychogenic syndrome have been reported and it is therefore important to carefully plan the setting where mass vaccination campaigns will be implemented.…”
Section: Human Papillomavirus (Hpv) Vaccinationmentioning
confidence: 99%
“…6 These vaccines have been incorporated into public vaccination policies with 3 doses schemes administered over a period of 6 months. 7 High effectiveness of the tetravalent vaccine in preventing genital warts has been observed in Sweden 8 and Denmark, 9 and a herd immunity effect has been documented in Australia. 10 In the United States, 4 y after the introduction of a vaccination program, 56% reductions in HPV prevalence have been observed in women between 14 and 19 y of age despite the low coverage rates achieved for the second and third doses.…”
Section: Introductionmentioning
confidence: 99%